A Modern Approach to the Elaboration and Selection of Strategic Alternatives for Resource Regions - Kryukov, Valeriy Anatolyevich; Sevastyanova, Anastasiya Yegorovna; Tokarev, Anatoliy Nikolayevich; Shmat, Vladimir Vitalyevich (Economy of Regions, 2017)
For many countries and regions (both in Russia and abroad), natural resources are the crucial factor for socio-economic development. The role and significance of natural resources in the economy of different areas substantially depend on the institutional environment, including the resource regime. Today, we have a qualitative complication of conditions for mineral resources exploitation, we start to develop new, non-traditional types of resources, which haven’t been available (or demanded) earlier for the economic and technological reasons. The changes in the characteristics of natural objects, as well as the increasing of uncertainty in the resource sector, actualize the search for alternatives of the development of resource-type regions and for the elaboration of appropriate strategies. In new conditions of resource regions, it is necessary to place emphasis on the aspects of expanded specific understanding of inclusiveness. It implies the possibility of active participation of regional authorities in the management and regulation of the mineral complex, as well as their involvement in the development of the association of a wide range of communities. These communities consist of the organizations representing the interests of indigenous peoples as well as professional communities: industry associations, environmental organizations, representatives of the innovation industry. Modern approaches to the elaboration of strategic directions for the resource regions development (primarily based on the development of the mineral industry) should be based on sustainable development principles, the principles of inclusiveness and the need for innovations. As a result of the convergence of these characteristics, a new socio-economic concept is formed. This concept can be defined as the harmonious development that is extremely important for the Russian regions. The proposed approach can be used for the elaboration of strategic alternatives of the development of resource regions.